Life-cycle inventory for hydroelectric generation: a Brazilian case study - Ribeiro, Flavio de Miranda [UNESP]; da Silva, Gil Anderi [UNESP] (Elsevier B.V., 2010)
Representative Life-Cycle Inventories (LCIs) are essential for Life-Cycle Assessments (LCAs) quality and readiness. Because energy is such an important element of LCAs, appropriate LCIs on energy are crucial, and due to the prevalence of hydropower on Brazilian electricity mix, the frequently used LCIs are not representative of the Brazilian conditions. The present study developed a LCI of the Itaipu Hydropower Plant, the major hydropower plant in the world, responsible for producing 23.8% of Brazil's electricity consumption. Focused on the capital investments to construct and operate the dam, the LCI was designed to serve as a database for the LCAs of Brazilian hydroelectricity production. The life-cycle boundaries encompass the construction and operation of the dam, as well as the life-cycles of the most important material and energy consumptions (cement, steel, copper, diesel oil, lubricant oil), as well as construction site operation, emissions from reservoir flooding, material and workers transportation, and earthworks. As a result, besides the presented inventory, it was possible to determine the following processes, and respective environmental burdens as the most important life-cycle hotspots: reservoir filling (CO(2) and CH(4) emission: land use); steel life-cycle (water and energy consumption; CO, particulates, SO(x) and NO(x) emissions); cement life-cycle (water and energy consumption; CO(2) and particulate emissions); and operation of civil construction machines (diesel consumption; NO(x) emissions). Compared with another hydropower studies, the LCI showed magnitude adequacy, with better results than small hydropower, which reveals a scale economy for material and energy exchanges in the case of ltaipu Power Plant. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Life-cycle assessment (LCA); Life-cycle inventory (LCI); Electricity; Hydropower; Hydroelectricity